MANAJEMEN SUMBER DAYA MANUSIA STRATEGIK: KESESUAIAN ANTARA STRATEGI SUMBER DAYA MANUSIA DENGAN STRATEGI BISNIS - Agus Fauzi (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2016)
This article aims to examine the new role of human resources, responsible for building organizational capability utilizing external opportunities. The new role of human resources as a strategic partner, administrative expert, employee champion, and change agents in each organization is different, including the heterogeneity or homogeneity of implementation and relations between various roles in question. Methods and approaches in this study using the study of literature. Literature in this study took on a variety of empirical research journals and books that discuss the new role of human resource management. Human resource professionals, often referred to as a business partner, which is narrowly defined as human resource professionals who work with general managers to implement the strategy as a strategic partner. This time understanding the business partners has changed a lot, not only as a strategic partner, but also as an administrative expert, employee champion and change agent. Results of the study also found that there are four levels of conformity (alignment) between the functions of human resources with strategic planning (business) namely administrative linkage, linkage one-way, two-way linkage, and integrative Linkage.